Effectiveness of a bite-sized web-based intervention to improve healthcare worker wellbeing: A randomized clinical trial of WISER - Sexton, J. Bryan; Adair, Kathryn C.; Cui, Xin; Tawfik, Daniel S.; Profit, Jochen (Frontiers in Public Health, 2022)
Importance Problems with the wellbeing of healthcare workers (HCWs) are widespread and associated with detrimental consequences for the workforce, organizations, and patients. Objective This study tested the effectiveness of the Web-based Implementation for the Science of Enhancing Resilience (WISER) intervention, a positive psychology program, to improve six dimensions of the wellbeing of HCWs. Design We conducted a randomized controlled trial of HCWs between 1 April 2018 and 22 July 2019. Cohort 1 received WISER daily for 10 days. Cohort 2 acted as a waitlist control before receiving WISER. Setting Web-based intervention for actively employed HCWs across the United States. Participants Eligibility criteria included being ≥18 years old and working as a HCW. Each participant was randomized to start the intervention or serve as a waitlist control for 14 days before starting the intervention. Interventions Cohorts received links via 10 texts exposing them to introductory videos and positive psychology exercises (3 good things, cultivating awe, random acts of kindness, cultivating relationships, and gratitude letters). Main outcomes and measures The primary outcome was emotional exhaustion; secondary outcomes included depressive symptoms, work-life integration, happiness, emotional thriving, and emotional recovery. All outcomes were assessed at baseline, 1-week post-intervention (primary endpoint), and 1, 6, and 12-month post-intervention. Outcomes were measured using six validated wellbeing instruments, rescaled to 100-point scales for comparison. Six items assessed participants' WISER experience. The analysis employed mixed-effects models. Results In cohorts 1 and 2, 241 and 241 initiated WISER, and 178 (74%) and 186 (77%) completed the 6-month follow-up, respectively. Cohort populations were similar at baseline, mostly female (81; 76%) and nurses (34; 32%) or physicians (22; 23%), with 1–10 years of experience in their current position (54; 52%). Relative to control, WISER significantly improved depressive symptoms [−7.5 (95%CI: −11.0, −4.0), p < 0.001], work-life integration [6.5 (95%CI: 4.1, 8.9), p < 0.001], happiness [5.7 (95%CI: 3.0, 8.4), p < 0.001], emotional thriving [6.4 (95%CI: 2.5, 10.3), p = 0.001], and emotional recovery [5.3 (95%CI: 1.7, 8.9), p = 0.004], but not emotional exhaustion [−3.7 (95%CI: −8.2, 0.8), p = 0.11] at 1 week. Combined cohort results at 1, 6, and 12 months showed that all six wellbeing outcomes were significantly improved relative to baseline (p < 0.05 for all). Favorable impressions of WISER were reported by 87% of participants at the 6-month post-assessment. Conclusion and relevance WISER improved HCW depressive symptoms, work-life integration, happiness, emotional thriving, and emotional recovery. Improvements in all HCW wellbeing outcomes endured at the 1-, 6-, and 12-month follow-ups. HCW's impressions of WISER were positive. Clinical trials number https://clinicaltrials.gov/ct2/show/, identifier: NCT02603133. Web-based Implementation for the Science of Enhancing Resilience Study (WISER).